Pengembangan Media Pembelajaran Teka-Teki Silang IPA Terpadu Untuk Siswa Kelas VII SMPN 56 Merangin : (Development of Integrated Science Crossword Learning Media for Class VII Students of SMPN 56 Merangin) - Eni Yulianti; Andriyanto Andriyanto (BIODIK, 2021)
Learning media is a teacher's tool in delivering teaching materials. Fun learning media will make students happy in learning. This will certainly make student learning outcomes better. The purpose of this research is to produce an integrated science crossword puzzle learning media product on the material classification of living things and material classification and changes for class VIII SMP N 56 Merangin which is valid, practical and effective. The method used to produce these products is the Development research method, namely the four-D development model. The four-D development model consists of four stages, namely the definition stage, the design stage, the development stage and the dissemination stage. The results of this product validation are very valid from the language aspect with a value of 92.5%, material aspects 85.4%, presentation and graphic aspects 85%. The criteria for the practicality of the media are very practical and the completeness of learning outcomes using the Integrated Science TTS media is 75%. Abstrak. Media belajar adalah alat bantu guru dalam menyampaikan materi ajar. Media belajar yang menyenangkan akan membuat siswa menjadi senang dalam belajar. Hal ini tentu akan membuat hasil belajar siswa menjadi baik. Tujuan dari penelitian ini adalah menghasilkan produk media pembelajaran Teka-Teki Silang IPA Terpadu pada materi klasifikasi makhuk hidup dan klasifikasi materi dan perubahannya untuk kelasVII SMP N 56 Merangin yang valid, praktis dan efektif. Metode yang digunakan untuk menghasilkan produk tersebut adalah metode penelitian Pengembangan yaitu model pengembangan four-D. Model pengembangan four – D terdiri dari empat tahap yaitu tahap pendefinisian (define), tahap perancangan (design), tahap pengembangan (develop) dan tahap penyebaran (disseminate). Hasil validasi produk ini adalah sangat valid dari aspek bahasa dengan nilai 92,5 %, aspek materi 85,4 %, aspek penyajian dan kegrafikan 85 %. Kriteria praktikalitas media sangat praktis dan ketuntasan hasil belajar menggunakan media TTS IPA Terpadu 75 %.